Length–weight relationships of freshwater fishes of the Alto Madre de Dios River (Manu Biosphere Reserve, Peru) - Tobes, Ibon (2016)
The present work provides the estimates of morphometric relationships for 22 native freshwater fish species (11 Characidae, five Loricariidae, two Heptapteridae, one Astroblepidae, one Crenuchidae, one Curimatidae and one Erythrinidae) collected in the Alto Madre de Dios River (Cuzco and Madre de Dios, Peru) in June 2012 using a mobile backpack electrofishing unit. These are the first length–weight relationships reported for 24 species, mostly endemic to the Amazonian basin. Knowledge regarding these biometric relationships can be relevant in the management and conservation of the local fishes and fisheries. © 2016 Blackwell Verlag GmbH